2018
DOI: 10.1111/pce.13367
|View full text |Cite
|
Sign up to set email alerts
|

Stomatal behaviour and stem xylem traits are coordinated for woody plant species under exceptional drought conditions

Abstract: Isohydry (maintenance of plant water potential at the cost of carbon gain) and anisohydry (gas exchange maintenance at the cost of declining plant water status) make up two ends of a stomatal drought response strategy continuum. However, few studies have merged measures of stomatal regulation with xylem hydraulic safety strategies based on in situ field measurements. The goal of this study was to characterize the stomatal and xylem hydraulic safety strategies of woody species in the biodiverse Mediterranean-ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
49
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(52 citation statements)
references
References 53 publications
1
49
1
1
Order By: Relevance
“…Consequently, all 10 species would be classified as being isohydric according to this definition. Although anisohydric behaviour with negative HSM ST has been reported in some species (Pivovaroff et al, ; Skelton et al, ), there is mounting evidence that stomatal closure occurs prior to the occurrence of embolism in many species (Choat, Brodribb, et al, ; Martin‐StPaul et al, ; Sperry et al, ). Considering that embolism recovery in woody plants may be limited (Choat, Nolf, et al, ; Creek, Blackman, Brodribb, Choat, & Tissue, ; Li, Blackman, Rymer, et al, ), the occurrence of “extreme” anisohydry, where stomata remain open beyond the point where significant cavitation occurs, may be rare.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Consequently, all 10 species would be classified as being isohydric according to this definition. Although anisohydric behaviour with negative HSM ST has been reported in some species (Pivovaroff et al, ; Skelton et al, ), there is mounting evidence that stomatal closure occurs prior to the occurrence of embolism in many species (Choat, Brodribb, et al, ; Martin‐StPaul et al, ; Sperry et al, ). Considering that embolism recovery in woody plants may be limited (Choat, Nolf, et al, ; Creek, Blackman, Brodribb, Choat, & Tissue, ; Li, Blackman, Rymer, et al, ), the occurrence of “extreme” anisohydry, where stomata remain open beyond the point where significant cavitation occurs, may be rare.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, all 10 species would be classified as being isohydric according to this definition. Although anisohydric behaviour with negative HSM ST has been reported in some species (Pivovaroff et al, 2018;Skelton et al, 2015), there is mounting evidence that stomatal closure occurs prior to the occurrence of embolism in many species (Choat, Brodribb, et al and relative stomatal conductance (closed circle, pink band) responds to water potential in two species (Figure 2a,b) with contrasting Hydroscape area ( Figure 2c,d). Shaded bands represent confidence interval for stem and stomatal response to water potential and denote standard error for leaf response.…”
Section: Comparison Of Metricsmentioning
confidence: 95%
See 2 more Smart Citations
“…Manrique‐Alba et al () compared stem radial growth between an isohydric and an anisohydric conifer species and found that the different strategies translate into alternative growth and water storage strategies under drought and heat. In another field study, Pivovaroff, Cook, and Santiago () showed that the degree of isohydry/anisohydry was correlated with the size of hydraulic safety margins across species in a Mediteranean‐type ecosystem in California. More isohydric species had larger hydraulic safety margins, implying that maintenance of a more conservative hydraulic strategy occurs at the expense of carbon gain.…”
mentioning
confidence: 99%